Manufacturing sustainability and life cycle management in the production of acoustic guitars. (5th May 2009) - French, Mark; Handy, Rod; Jackson, Mark J.
The manufacture of stringed instruments has strong elements of traditional practice, particularly in the choice of materials from which the instruments are made. While man-made materials have been used in successful instruments, they are overwhelmingly made of wood. The preferred species include Sitka spruce, mahogany, rosewood and maple. Furthermore, the grade of materials used for instruments is extremely high, only one step below that used for the load-carrying structures of aircraft. The ideal piece of wood is straight-grained and without imperfections such as knots, checks or discolouration. The growth rings should be close together, so slow-growing trees are preferred. The result is that trees yielding instrument-quality wood have been heavily logged and are becoming very scarce. This is reflected in the rising prices of instrument grade wood. At this writing, a master-grade top blank for a single acoustic guitar can cost up to 300. The retail value of guitars sold in the USA is approaching 1 billion per year, so the demand for materials is not going to ease soon. Clearly, the industry must change its practices if it is to sustain production. Several fundamental changes are required. The strong prejudice against laminated materials must be overcome. High grade plywood exhibits structural properties and uniformity that would make it ideal for instrument manufacture, but its use is limited to student grade instruments. The Convention on International Trade and Endangered Species (CITES) outlines the terms under which traditional species can be legally and sustainably harvested, but it limits production volumes and the temptation to skirt the regulations is strong. Thus, another required change is to switch to fast-growing species. Finally, manufacturing processes must be modified and life cycle management procedures should be implemented to allow for the effective and efficient use of smaller, younger trees.